2018
DOI: 10.1007/s12328-018-0834-8
|View full text |Cite
|
Sign up to set email alerts
|

A case of small intestinal neuroendocrine carcinoma diagnosed using double-balloon endoscopy with long-term survival

Abstract: Neuroendocrine neoplasms, including neuroendocrine tumors (NETs) and neuroendocrine carcinomas (NECs), are rare epithelial tumors with a predominant neuroendocrine differentiation. Compared with NETs, NECs have been reported to be rarer and have a poorer prognosis. We present a rare case of small bowel NEC diagnosed using double-balloon endoscopy (DBE) and the long-term survival accomplished via intensive therapy. DBE revealed an ulcerative tumor in the deep jejunum, and biopsy specimens showed large and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, BAE enables direct observation of these small intestinal lesions, and also permits biopsy and endoscopic therapy, such as stent placement and endoscopic tattooing for subsequent surgical therapy[5,6]. A previous study reported the incidence of small intestinal tumors detected by BAE[6,7]; however, the endoscopic characteristics of small intestinal tumors have been reported only in a limited number of case reports[8-10], and the details of these characteristics are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BAE enables direct observation of these small intestinal lesions, and also permits biopsy and endoscopic therapy, such as stent placement and endoscopic tattooing for subsequent surgical therapy[5,6]. A previous study reported the incidence of small intestinal tumors detected by BAE[6,7]; however, the endoscopic characteristics of small intestinal tumors have been reported only in a limited number of case reports[8-10], and the details of these characteristics are still unknown.…”
Section: Introductionmentioning
confidence: 99%